Mechanical stability of granite as thermal energy storage material: An experimental investigation. (15th April 2019) - Li, Baiyi; Ju, Feng; Xiao, Meng; Ning, Pai
Highlights: Mechanical deterioration was explained by crack propagation in different cycles. Thermal cycle effect on fracture modes of granite was investigated. The brittle granite became ductile after exposed to cyclic high temperature. Granite withstood thermal cycled treatment and still had sufficient strength. Abstract: Thermal energy storage integrated with solar power plants can be considered as a promising way in improving the efficiency and overcoming the intermittency of solar power plants at low costs. It is proposed that natural rock is good and suitable for thermal energy storage material in concentrating solar power plants at high temperature of approximately 500–700 °C. However, more attention has been devoted to thermal capacity and conductivity when selecting the potential rock, while little work has been done in the field of rock mechanical behaviors in this particular situation where rock need to keep stable after undergoing cyclic high temperature. This paper aims to evaluate the potential of granite to be thermal energy storage material in mechanical aspect, by analyzing the mechanical characteristics of granite after exposed to high-temperature treatment with temperature cyclically changing between 20 °C and 650 °C. Uniaxial compression tests were carried out to reveal the effect of thermal cycles on the crack damage development, strength decrease and failure mode of granite. The results showed that, micro cracks would generate in granite after exposed to high temperature and consequently lead to the deterioration of rock mechanical characteristics, especially in the first thermal cycle when there were dramatically drops in the peak strength and elastic modulus of granite. The deterioration reached almost constant when granite was thermally cycled more than 20 times. The changes of mechanical behaviors were explained through the microstructure measured by SEM. Thermal cycle effects on the failure mode of granites were investigated by monitoring acoustic emissions and analyzing fracture surface during uniaxial compression test. The brittle-ductile transition of granite was enhanced with the increase of thermal cycle.